Chitooligosaccharides from squid pen prepared using different enzymes: characteristics and the effect on quality of surimi gel during refrigerated storage - Avtar Singh; Soottawat Benjakul; Thummanoon Prodpran (Food Production, Processing and Nutrition, 2019)
Abstract Chitooligosaccharides (COS) from squid pen produced using amylase, lipase and pepsin were characterized. COS produced by 8% (w/w) lipase (COS-L) showed the maximum FRAP and ABTS radical scavenging activity than those prepared using other two enzymes. COS-L had the average molecular weight (MW) of 79 kDa, intrinsic viscosity of 0.41 dL/g and water solubility of 49%. DPPH, ABTS radical scavenging activities, FRAP and ORAC of COS-L were 5.68, 322.68, 5.66 and 42.20 μmol TE/g sample, respectively. Metal chelating activity was 2.58 μmol EE/g sample. For antibacterial activity, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of COS-L against the targeted bacteria were in the range of 0.31–4.91 mg/mL and 0.62–4.91 mg/mL, respectively. Sardine surimi gel added with 1% (w/w) COS-L showed the lower PV, TBARS and microbial growth during 10 days of storage at 4 °C. COS-L from squid pen could inhibit lipid oxidation and extend the shelf-life of refrigerated sardine surimi gel. Graphical abstract